Diseño y construcción de un sistema de destilación solar tipo cascada para la obtención de 180 ml/día de agua destilada tipo IV - Luna Peñafiel, Jonathan Fabricio (2017)
The following investigation consists on the obtention of water type IV. In order to get of distilled water, a balance of energy considering heat flows involved between water tanks and cover was presented. Afterwards, current formula was used to develop calculations explaining every process of simplification or replacement, making them more concise in their structure. Equipment performance tests were carried out for an extended period of time in favorable conditions such as sunny days as well as in unfavorable conditions such as rainy days. The gathered data corroborated the foreseen energy balance obtaining , making its industrial investment profitable. Moreover, its consume was considerably low in comparison to electric distillers, which is why the equipment is eco-friendly. In relation to the radiation incident in different days, while it has a high value, temperatures in water are superior to 70 °C, same situation happens with the absorbent plate and the glass cover, which temperatures rise as the following: the former exceeds temperatures of 85 °C and the later maintains its rage from 40 °C to 50 °C. In this conditions, 60 ml of water can be obtained in approximately 20 minutes. On the contrary, in days with low radiation, values in water, absorbent plate and glass cover drop to 27 °C, 30 °C and 20 °C respectively, getting on average 10 ml of distilled water every 20 minutes. The cascade type distillation design in comparison to distillation results reached by Tabuada and Flores, shows a compact size that allows the prompt heat absorption obtaining a higher quantity of distillation in a shorter period of time; its yield is 61% while the performance of the double deck design is 35%